Low‐Valent Titanium Species Stabilized with Aluminum/Boron Hydride Fragments. Issue 4 (2nd December 2021) - del Horno, Estefanía; Jover, Jesús; Mena, Miguel; Pérez‐Redondo, Adrián; Yélamos, Carlos
Abstract: Low‐valent titanium species were prepared by reaction of [TiCp*X3 ] (Cp*=η 5 ‐C5 Me5 ; X=Cl, Br, Me) with LiEH4 (E=Al, B) or BH3 (thf), and their structures elucidated by experimental and theoretical methods. The treatment of trihalides [TiCp*X3 ] with LiAlH4 in ethereal solvents (L) leads to the hydride‐bridged heterometallic complexes [TiCp*(μ‐H)2 (μ‐H)2 AlX(L)2 ] (L=thf, X=Cl, Br; L=OEt2, X=Cl). Density functional theory (DFT) calculations for those compounds reveal an open‐shell singlet ground state with a Ti−Ti bond and can be described as titanium(II) species. The theoretical analyses also show strong interactions between the Ti−Ti bond and the empty s orbitals of the Al atom of the AlH2 XL fragments, which behave as σ‐accepting (Z‐type) ligands. Analogous reactions of [TiCp*X3 ] with LiBH4 (2 and 3 equiv.) in tetrahydrofuran at room temperature and at 85 °C lead to the titanium(III) compounds [TiCp*(BH4 )(μ‐X)2 ] (X=Cl, Br) and [TiCp*(BH4 )(μ‐BH4 )2 ], respectively. The treatment of [TiCp*Me3 ] with 4 and 5 equiv. of BH3 (thf) produces the diamagnetic [TiCp*(BH3 Me)2 (μ‐B2 H6 )] and paramagnetic [TiCp*(μ‐B2 H6 )2 ] complexes, respectively. Abstract : The structure and bonding of bimetallic half‐sandwich titanium(III) and titanium(II) complexes stabilized by boron (BH4 −, BH3 Me −, B2 H6 2− ) or aluminum (μ‐H)2 AlXL) (X=Cl, Br; L=thf, OEt2 ) hydride ligands are reported. DFT calculations on the hydride‐bridged Ti(II)−Al compounds reveal a strong electron density donation from the Ti−Ti bond to the empty s orbitals of the Al atoms. These unprecedented M−M→Z type interactions could be common for bi‐ or multimetallic low‐valent early transition metal derivatives.